2021
DOI: 10.1016/j.clinbiomech.2021.105366
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanical properties of the Achilles tendon in senior badminton players: Operated vs. non-injured tendons

Abstract: Background:The aim of this study was to describe the differences in structural and mechanical properties between operated and non-injured Achilles tendons in senior badminton players who had had Achilles tendon surgery and had returned to play. Methods: Eighteen players (age = 48.9(10.0)years), assigned to the unilateral Achilles tendon rupture group and 177 non-injured players (age = 55.4(9.4)years), assigned to the control group. A Logiq®S8 ultrasound was used to study tendon structure and elastography index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Several studies have shown the feasibility of using the MyotonPRO device to monitor the mechanical properties of skeletal muscles in athletes, healthy young and older adults, and individuals with some pathology [ 6 , 7 , 8 ]. These studies analysed muscle mechanical properties using the standard protocol with ten brief mechanical stimuli, and it demonstrated moderate to excellent intra- and inter-evaluator reliability (intra-class correlation coefficients (ICC) ranging from 0.62 to 0.99) [ 5 , 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the feasibility of using the MyotonPRO device to monitor the mechanical properties of skeletal muscles in athletes, healthy young and older adults, and individuals with some pathology [ 6 , 7 , 8 ]. These studies analysed muscle mechanical properties using the standard protocol with ten brief mechanical stimuli, and it demonstrated moderate to excellent intra- and inter-evaluator reliability (intra-class correlation coefficients (ICC) ranging from 0.62 to 0.99) [ 5 , 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The elastographic index (EI) of the PT was evaluated in three ROIs (at 25%, at 50% and at 75% of the total length PT; Figure 3 ) and in the same position as in the previous measurement by real-time elastography (LOGIQ E9, GE Healthcare, Milwaukee, WI, USA). This measurement was made following the methodology of previous research [ 24 , 25 , 26 , 27 , 28 ]. The average of the three measurements was stated.…”
Section: Methodsmentioning
confidence: 99%
“…10 The ATR incidence is always at a high level in badminton sport, because of a large number of directional lunges, jumping, and landing movements. 11 Evidence has been reported that ATR will cause persistent tendon elongation and it is associated with biomechanical deficits such as decreased plantar flexor muscle strength/volume, decreased ankle joint proprioception, and reduced AT stiffness. 12 The gait abnormalities and functional deficits have been found in the ruptured side compared with the contralateral side and healthy control group.…”
Section: Introductionmentioning
confidence: 99%